2021
DOI: 10.7150/jca.48906
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phospholipid metabolism in exosomes of hormone-sensitive and hormone-resistant prostate cancer cells

Abstract: Background: To explore the changes in lipids in exosomes of hormone-sensitive and hormone-resistant prostate cancer cells and develop an inexpensive and rapid technique for screening lipid-based biomarkers of prostate cancer. Methods: Exosomes were extracted from LnCap, PC 3 and DU-145 cells, and their lipid composition was analyzed quantitatively using high-throughput mass spectrometry. Exosomes released by LnCap prostate cancer cells were also purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Metabolomics (Figure S11, Supporting Information) and proteomics (Figure S12, Supporting Information) on exosomes isolated from serum‐containing and serum‐deprived media of old MEFs (passage 8) revealed that the metabolomic profile of exosomes from starvation group was significantly different from that of the control group, and differential proteins were mainly enriched in nucleic acid metabolic process. Lysophosphatidylcholine (LPC) is a harmful metabolite of lipids and is associated with inflammation [ 38 ] and oxidative stress. [ 39 ] This is a representative obsolete molecule highly accumulated in the exosomes expelled by the starvation old cells.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics (Figure S11, Supporting Information) and proteomics (Figure S12, Supporting Information) on exosomes isolated from serum‐containing and serum‐deprived media of old MEFs (passage 8) revealed that the metabolomic profile of exosomes from starvation group was significantly different from that of the control group, and differential proteins were mainly enriched in nucleic acid metabolic process. Lysophosphatidylcholine (LPC) is a harmful metabolite of lipids and is associated with inflammation [ 38 ] and oxidative stress. [ 39 ] This is a representative obsolete molecule highly accumulated in the exosomes expelled by the starvation old cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors provide their data as a percentage of the total phospholipids, and absolute values are usually expressed as the amount of phospholipid per 10 6 cells or otherwise the tissue mass are not available. In the case of prostate cells, the comparison of the percentage content of individual GPLs with the results of some authors [ 45 , 46 ] showed a large convergence, but there were considerable differences with the results of other authors [ 47 ]. It was presumed that, apart from the various methods of determination of GPL, the underlying cause was the various lipid isolation procedures applied, which was also demonstrated in this study.…”
Section: Resultsmentioning
confidence: 73%
“…An overabundance of PUFAs can cause the Fenton reaction to convert them into hydroxyl radicals, which in turn can cause an overabundance of lipid peroxide and, in turn, cause cells to enter ferroptosis ( Dierge et al, 2021 ; Mishima and Conrad, 2022 ). Phosphatidyl ethanolamine (PE) makes up roughly 15%–25% of the phospholipids in the membranes of other organelles compared to about 40%–45% of the total phospholipids in the inner membrane of mitochondria ( Feng and Stockwell, 2018 ; Yi et al, 2021 ). Data indicates that PE contributes to the ferroptosis triggered by arachidonic acid (AA) and its analogues.…”
Section: Distinctive Features Of Ferroptosismentioning
confidence: 99%